Architecture of the Indonesia Welfare State: The reflection of 20 years of Indonesia Reformation Era - Budhi Dharma (Laboratorium Ilmu Kesejahteraan Sosial FISIP UHO Kendari, 2024)
After Asian Economic Crisis (AEC) hit many of Asian countries in 1997, Indonesia and Asian countries are experiencing crisis and change, Indonesia had transformed its economic and political structured. From centralistic to be more decentralised. Indonesia has produced various economic policy to recover the destructive of the crisis which has impacted not only on economic dimension but also other dimensions. Alongside of massive economic and political changing, Indonesia also realised to reform its social policy system to protect people especially the lower middle class during the crisis. During 20 years from 1998-2018 Indonesia has a massive transformation in terms of social policy and strengthening their architecture of welfare state. Using several data from various journal articles and research reports which has been analysed through qualitative content analysis this paper is aimed to understand how Indonesia has been committing to address absolute poverty and income inequality. The results of the study found that Indonesia has transforming their social policy to be more institutionalised to tackle poverty and income inequality.